Peter Gavin Hall. 20 November 1951—9 January 2016. (30th April 2018) - Robinson, John; Welsh, Alan H.
Abstract : In the 40 years of his research career, Peter Hall produced work in both probability and statistics, the breadth and depth of which must be regarded as phenomenal. He displayed extraordinary technical skills together with remarkable intuition in developing and applying multifaceted mathematical approaches in the whole of his work. The impact of this wide-ranging use of powerful mathematical methods has had a profound effect on much of modern mathematical statistics. After completing his DPhil at Oxford, he remained in Australia for almost all of his career although he was renowned as one of the major international figures in probability and statistics. Peter was a mentor to a large group of postgraduate students and post-doctoral colleagues, giving encouragement and guidance, and he attracted many research visitors, contributing greatly to the whole of Australian statistical research. Remarkably, given his immense research output, he took a significant role both in editorial duties in major international journals and in advocacy for mathematics and statistics in Australia. Peter was a man of great charm whose modest demeanour belied his staggering abilities. His loss to mathematics and statistics is great, but is matched by the personal loss to us and to his many friends.